Genetic characterization of four strains porcine circovirus-like viruses in pigs with diarrhea in Hunan Province of China - Ji, Chihai; Zeng, Meng; Wei, Yingfang; Lv, Xiaocheng; Sun, Yuan; Ma, Jingyun (Frontiers in Microbiology, 2023)
In this study, we detected a circular replication-associated protein (Rep)-encoding single-stranded (CRESS) DNA virus (named Po-Circo-like (PCL) virus) in intestinal tissue and faecal samples of pigs. PCL virus contains a single-stranded DNA genome, and ORF1 encodes the Rep and not the typical capsid protein encoded in PCV. The Rep protein may be responsible for viral genome replication. In addition, PCL virus may be one of the pathogens causing diarrhea symptoms in pigs. We identified four strains of PCL virus in two different pig farms with severe diarrhea outbreaks in Hunan Province, China. The strains in this study share 85.7%–99.7% nucleic acid identity and 84.7%–100% amino acid identity with Rep of the reference strains. A multiple sequence alignment of these PCL viruses and Bo-Circo-like CH showed a identity of 93.2% for the Rep protein, and the nucleotide identity was 86.7–89.3%. Moreover, Bo-Circo-like CH and HN75, HN39-01, HN39-02 had similar stem-loop sequences. In conclusion, the present study is the first detailed report of the PCL virus in Hunan provinces, which is a potential new virus in pigs that might be involved in cross-species transmission. Further investigation is needed to determine the pathogenesis of this virus and its epidemiologic impact.